The corporeal and monstrosity of supernatural entities: towards a socio-functional illustration of Pontianak in Tunku Halim's “Horror Stories” - Marlina Jamal, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Female characters in horror fiction are often constructed by the image of their body, which emphasises an innermost marker as sexual beings. The current study focuses on the depiction of Pontianak, a supernatural entity famous in Malay folklore, in selected short stories written by Tunku Halim. A critical discourse method, Fairclough’s (1995) three-dimensional framework, was incorporated to analyse data. Lexical structures, as expressed in the selected texts, are analysed, and findings demonstrate the existence of corporeal and monstrosity elements associated with Pontianak. The entity is sexualised and depicted as connected with evil, as she resorts to violence to satisfy her desires, ultimately disparaging the patriarchal cocoon in which a Malay woman is confined. The character portrayal of the Pontianak in Malay folklore exhibits elements of sexual discrimination and evil, as seen in the emphasis on her physical attributes and characteristics. This portrayal blurs the boundaries between supernatural entities and sexual magnetism, highlighting the interconnection between gender and power dynamics. This representation highlights the notion that to escape this oppression, the realm of horror becomes crucial. Within this realm, female characters possess destructive abilities and the capacity for retribution, but this can only be achieved through their association with the supernatural world of malevolent forces. These narratives provide a platform for exploring themes of empowerment and resistance against patriarchal dominance.